Profile of Staphylococcus aureus Originating from Nasal Cavity Swabs of Food Handlers at the University of Mataram Canteen - Candrawati, Tania Happy; Hasbi, Nurmi; Rosyunita, Rosyunita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Staphylococcus aureus is a Gram-positive bacteria that is widespread on human skin and mucosa and can cause a range of ailments, from food poisoning to serious and life-threatening infections. Food handlers are directly linked to food hygiene since they can be a source of infection. The purpose of this study was to detect the presence of S. aureus bacteria in the nasal cavity of canteen handlers in the University of Mataram. This study used a cross-sectional descriptive research design with a population of all food handlers at the University of Mataram canteen. This study was conducted through the stages of isolation, culture, Gram staining, and biochemical detection. The sampling technique used in this study was purposive sampling. This study was conducted on 10 samples of nasal cavity swabs of food handlers in the canteen of the University of Mataram with 5 (50%) positive samples of S. aureus. Meanwhile, the other 5 (50%) samples were indicated to be types of Staphylococcus sp. other species. It can be concluded that the presence of S. aureus was found in food handlers at the University of Mataram Canteen and food handlers are also expected to improve the application of hygiene and sanitation to themselves.